Formulas! Formulas! Everywhere! A few activities to introduce area - Moyer, Todd O; Krach, R. Michael (Ohio Journal of School Mathematics, 2022)
This article describes activities that can be used to introduce the concepts of perimeter and area with conceptual understanding for students in grades 4 through 9. The transformations of reflection and rotation are used to build this understanding.